2017
DOI: 10.1080/15569527.2017.1311337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topiramate on choroidal thickness and anterior chamber parameters in the treatment of patients with migraine

Abstract: The study revealed increased CT and altered anterior chamber parameters and IOP due to topiramate therapy. Therefore, the patients using topiramate should be carefully monitored by an ophthalmologist considering the possible side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
2
1
Order By: Relevance
“…The findings of our study were in agreement with many previous case reports [18][19][20][21][22][23][24][25] and one of the previous published prospective studies [14]. On the contrary, other studies described changes that were not found in our study [15][16][17]. Those studies found significant ocular side effects induced by TPM including changes in the size of the ciliary body, ACD, RF, and IOP.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings of our study were in agreement with many previous case reports [18][19][20][21][22][23][24][25] and one of the previous published prospective studies [14]. On the contrary, other studies described changes that were not found in our study [15][16][17]. Those studies found significant ocular side effects induced by TPM including changes in the size of the ciliary body, ACD, RF, and IOP.…”
Section: Discussionsupporting
confidence: 93%
“…The difference in the ethnic groups might also explain the difference between the previous studies itself. Leung et al did not find any significant changes in a Chinese group of patients, like our study; however, the other two studies done for Turkish patients and the one done for Iranian patients found some significant changes in various ophthalmological parameters [14][15][16][17].…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In this study, iris adhesions were associated with TPM, moreover, iris disorder and iris atrophy were both showed positive signals, indicating that TPM probably had effect on iris. Some studies revealed that TPM could decrease or alter the anterior chamber angle, and these effects might be asymptomatic [19,20]. In this study, we verified the results with strong signals emerging in narrow anterior chamber angle and flat anterior chamber of eye.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, we presumed that TPM likely had no direct effect on the iris and instead affected the function of the iris from a common inflammatory mechanism. Certain studies have revealed that TPM can decrease or alter the anterior chamber angle, and these effects may be asymptomatic [22,23].…”
Section: Discussionmentioning
confidence: 99%